The effect of the floor and cage rearing systems on some production traits and livestock economics in broylers - M. Kenan Türkyılmaz; Ahmet Nazhgül; H. Erbay Bardakçtoğlu (Eurasian Journal of Veterinary Sciences)
This investigation was held to demonstrate the effects of cage and lloor systems on the abdominal fat and livestock economics on broylers, 200 Cobb 500 broyler chickens were consisted the matenal of the study. Average live weights at the sixth weeks of ages for the floor and cage groups were 2261,1 g and 2169,4 g respectively. Differences of Ihe live weights in the groups were statistically significant (p<0,01). Similar values (1,71) were obtained in the cage and floor groups for feed convertion rate. The average carcass weights and abdominal fat accumulation amounts were 1599,4 g and 1533,2 g and 21,6 g and 20,0 g for the floor and cage groups respectively. Differences among the groups for the abdominal fat weights were not statistically significant. Economic analyses were revealed that broylers in floor management were more profitable than cage systems.